Pore-scale investigation on the heat-storage characteristics of phase change material in graded copper foam. (September 2020) - Hu, Chengzhi; Li, Hongyang; Tang, Dawei; Zhu, Jie; Wang, Kuiming; Hu, Xianfeng; Bai, Minli
Highlights: Thermal behavior of solid-liquid phase change in graded copper foam was given. The enhancement mechanism of the graded metal foam is clarified. The effective thermal conductivity of composite PCM is analyzed. Abstract: The mechanisms responsible for the effect of metal foam, having a varying degree of porosity, on the phase change process in a phase change material (PCM) are not clearly understood. In this work, the pore-scale heat storage performance of the graded metal foams saturated with paraffin has been investigated using the computational fluid dynamics (CFD) method. The results demonstrate that the metal foam with a graded porosity accelerates the heat storage of PCM. In terms of the gradient dimension of the metal foam, the full melting time of the negative model 2 has been observed to be shortened by 2.6% as compared to the uniform model 1 and reduced by 15.5% as compared to the positive model 3. This is because the smaller the porosity of metal foam is, the faster the melting conducts. For the negative model, the relatively small porosity region is closer to the heat source than the large porosity region, which makes the heat transfer enhancement effect more evident than the weakening effect. Meanwhile, the full melting time shows an initial increasing trend, followed by a decrease for an increase in the porosity gradient difference. The optimal gradient difference is found to be −0.12 at the average porosity of 0.86 in this study.